Design of the wireless EV charger to meet the performance requirement of SAE J2954 standard - Patcharapon Kaewnoen; Supapong Nutwong; Nattapong Hatchavanich; Ekkachai Mujjalinvimut (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
To address the need for a reproducible design process for an efficient wireless electric vehicle (EV) charging system that guarantees compliance with the SAE J2954 standard, this paper proposes a systematic, flowchart-based optimization technique. Unlike methods that focus solely on coil performance, the proposed approach integrates standard-specific constraints, such as inductance and geometric limits, from the outset to ensure the final design meets stringent performance benchmarks for efficiency and misalignment tolerance. A circular flat spiral coil structure has been adopted for both the transmitter and receiver coils to enhance manufacturability and achieve uniform magnetic field distribution. A flowchart-based design technique has been developed to optimize key coil parameters, including the number of turns and coil diameters, subject to constraints of 200 µH inductance and a maximum outer diameter of 700 mm. Finite element analysis (FEA) simulations verify that the proposed design approach achieves maximum magnetic coupling under various air gap distances and misalignment conditions. An experimental validation of a 2-kW prototype demonstrates close agreement with simulations, achieving coil-to-coil efficiencies between 92.61% and 96.67%, and overall system efficiency exceeds 80% under all tested conditions. These results confirm that the proposed design method effectively meets performance requirements set by the SAE J2954 standard.